Optimizing diagnostic and management pathways for patients with eosinophilia of unknown origin: a multidisciplinary protocol for urgent and non-urgent evaluation - Silvia Sánchez-Ramón; Gloria Candelas Rodríguez; Jesús Gimeno Hernández; María Luisa González Gutiérrez; Sissy Fiorella Medina Salazar; Manuel Méndez Bailón; Begoña Navas Elorza; Ángel Nieto Sánchez; Teresa Robledo Echarren; Santiago Rueda Esteban; Marcos Oliver Fragiel Saavedra; María Dolores Zamora Barrios; et al. (Frontiers in Medicine)
IntroductionPersistent eosinophilia of unknown cause is a key feature of numerous health disorders. These conditions present diagnostic and management challenges, often leading to delayed treatment, increased morbidity and mortality and unnecessary healthcare costs. A systematic approach to patient flow can streamline the process from presentation with eosinophilia to triage management, in hospital settings.MethodsA proposal of a novel patient flow pathway was developed through a collaborative effort involving 15 diverse multidisciplinary specialists in a public-funded tertiary teaching hospital located in Madrid, Spain, for managing eosinophilic diseases. This pathway focuses on early identification and expedited referral circuits in severe cases of hypereosinophilia and early screening of primary immunodeficient patients to optimize the journey from initial presentation through diagnosis and initial management.ResultsThe proposed patient flow model is designed to be replicable in other hospital settings. Its implementation aims to facilitate timely diagnosis and reduce the preventable morbidity, mortality, suffering and economic burden associated with complex eosinophilic conditions.ConclusionThe development and implementation of a structured patient flow pathway for eosinophilia of unknown cause in a tertiary hospital setting demonstrates a significant step toward improving patient outcomes. This model serves as a template for other healthcare institutions seeking to enhance the management and care of patients with eosinophilic diseases.